Variabilidade espacial da uniformidade da lâmina de água aplicada por sistemas fixos de irrigação por aspersão - Tamagi, Jorge Tomoyoshi (2012)
Water application uniformity is an important factor to be considered in the evaluation of sprinkler irrigation systems. The uniformity depends on the type of sprinkler and its operational conditions, the display and space among the sprinklers on the field, and also the wind speed and direction during the water applying period. This work contributes to develop appropriate techniques for results evaluation in order to improve the system. The experiment was conducted at a farm called Floricultura & Mercado de Plantas Cascavel , north region of the city of Cascavel, Paraná, at 24º 55 04 South latitude and 53º 28 31 West longitude. Two water tanks of 5m³, a bomb, valves and hydrometer were installed. Two land areas were used, S1 and S2 of 10 x 10 m. On S1 were installed manometers, 100 collectors or pluviometers, 4 Super 10 blue nozzle pressure compensating sprinklers which, after 32 trials, were replaced by 4 Super 10 blue nozzle non pressure compensating sprinklers at 1.5m height, and the same on the area S2, in which the sprinklers were set at 1m height. During the sprinkler irrigation, at every 1h interval the amount of water in the collectors or pluviometers were collected and quantified by a graduated cylinder, and during this hour the wind condition, temperature and air humidity at the beginning from 10 to 10 minutes were recorded by a portable meteorological La Crosse Technology station. This study aimed to analyze by geostatistical methods if all data collected from water levels and irrigation uniformity by sprinkler irrigation have structures of spatial dependence. Results show that there is spatial variability for the average water depths in irrigation by aspersion with compensating sprinklers at 1.0 m height and average water depths in sprinkler irrigation with non-compensating sprinklers at 1.5m height. The existence of the special variability for the Christiansen uniformity coefficient (CUC), coefficient of uniformity of distribution (CUD) and statistical uniformity coefficient (CUE) was also verified. The best irrigation by aspersion was observed in the thematic maps produced for the Christiansen uniformity, coefficient of distribution and statistical uniformity coefficient with compensating sprinklers at 1,0 m high. It was observed that the wind speed affects the Christiansen coefficient of uniformity in an inverse ratio